KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA TEHIT SUATU ANALISIS KONTRASTIF - BOLTAL, PETRUS KALVIAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The research is entitled Interrogative sentences in English and Tehit language. This study is an attempt to describe and analyze the English and Tehit language which focuces on the interrogative sentences in relation to their form and function in both languanges based on Aarts and Aart’s theory and to contrast both language using by theory. The English and Tehit Language are two languages from different language families. English is included in Indo-European and Tehit Language is included in Austronesian. Each of them has its own characteristics. The English data have been collected from books, whereas the data of Tehit language have been collected by interviewing some informants. Then, the data are analyzed and described using contrastive analysis approach. The result shows that forms of interrogative sentences in English are yes-no question, tag question and interrogative-word question while in Tehit language has two forms namely interrogative word question and yes-no question. English and Tehit language have similarities, in the form of interrogative word question. The difference is in the placement of the word question: in English question word is at the beginning of sentence and Tehit language at the beginning and the end of sentence. Keywords: Interrogative sentences, English and Tehit Language, Contrastive Analysis